Carpentry - Koel, Leonard (American Technical Pub., 1997)
Carpentry, the professional's book of choice, provides a highly illustrated and straight-forward approach to step-by-step carpentry skill development. In addition to comprehensive coverage of trade practices, tools, equipment, and materials, this edition includes expanded coverage of OSHA requirements, insulating concrete forms (ICFs), vinyl siding installation, deck construction, stairway code requirements, and trade organizations.